2022
DOI: 10.3390/app12084064
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultrafine Blast Furnace Slag on the Microstructure and Chloride Transport in Cementitious Systems under Cyclic Drying–Wetting Conditions

Abstract: This paper presents experimental investigations into the effects of ultrafine blast furnace slag on microstructure improvements against chloride penetration in saturated and unsaturated cementitious systems exposed to cyclic drying–wetting conditions. The hydration kinetics of ultrafine slag powders and pore solution chemistry in slag-blended cementitious systems at different ages, together with the main hydration products and pore structure characteristics, were determined. The chloride profiles accounting fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…Figure 9b further illustrated the filling effect of the USL promoted the homogenisation of the paste and improved the uniform distribution of the USL particles in the UHPC. Further magnification of the BSE microscopy image of the pastes revealed that the USL particles were covered by the hydration products in Figure 9b, indicating that secondary hydration of the USL particles occurred and organically combined with the surrounding hydration products [28]. This is further evidence that the addition of 20% USL improved the homogeneity of the microstructure of the hydration products and increased the denseness of the cement paste, which is consistent with the results presented by the MIP and SEM analyses.…”
Section: Bse Analysissupporting
confidence: 86%
“…Figure 9b further illustrated the filling effect of the USL promoted the homogenisation of the paste and improved the uniform distribution of the USL particles in the UHPC. Further magnification of the BSE microscopy image of the pastes revealed that the USL particles were covered by the hydration products in Figure 9b, indicating that secondary hydration of the USL particles occurred and organically combined with the surrounding hydration products [28]. This is further evidence that the addition of 20% USL improved the homogeneity of the microstructure of the hydration products and increased the denseness of the cement paste, which is consistent with the results presented by the MIP and SEM analyses.…”
Section: Bse Analysissupporting
confidence: 86%